Entering Farmville: Finding Value in Social Games - Balnaves, Mark; Willson, Michele; Leaver, Tama (Australian and New Zealand Communication Association, 2012)
Social games—games that operate within social network sites (SNS) and draw on a user’s social graph—are a rapidly growing phenomena. According to AppData’s facebook applications report, Zynga’s social game, Farmville, as at the 15th March 2012, had 29,100,000 monthly active users (MAU) and 5,800,000 daily active users (DAU). The site also lists Farmville as no. 7 on the App leaderboard, and Zynga, the game designer, as no. 1 on the developer leaderboard with 245,429,908 MAU’s. These are not small numbers and clearly indicate a level of engagement and correspondingly, of revenue generation that warrant closer examination. However, the value of social gaming is far from just economic, with the experiences of game-play, and the broader social interactions possible surrounding social games, potentially creating value for the game company and players themselves in a number of different ways. This paper will explore the experience of the Zynga game Farmville, with particular focus on the question of value. Primary evidence will be drawn from the ethnographic experiences of one of the authors who spent several months immersed in Farmville as an explicitly positioned ethnographic researcher (as part of a larger ARC Linkage grant on social gaming on the internet). In order to situate these findings, this paper will also provide a brief history of the games leading to Farmville and explore the broader context of value creation in social games.